2000
DOI: 10.1093/deafed/5.3.237
|View full text |Cite
|
Sign up to set email alerts
|

The Pragmatic Skills of Profoundly Deaf Children

Abstract: This study investigated the ability of normally hearing students and two groups of profoundly deaf students, one using oral and one using signed communication, to employ a series of pragmatic skills required for effective face-to-face interaction. Specifically considered were the ability of listeners to request clarification, the ability of speakers to respond to requests, and the strategies speakers use at times of communication breakdown. Differences were found between the two groups suggesting that the prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 23 publications
0
67
3
Order By: Relevance
“…It therefore appears that a failure to take the listener's need into account is a problem that is experienced by some HI children, and may be more likely to occur as level of hearing loss increases (Elfenbein et al, 1994). The ability to take a listener's needs into account develops throughout the school years (Jeanes et al, 2000). Whether some HI children's inability to take the listener's needs into account is due to a developmental lag in referential communication skills or some other explanation cannot be determined from these results, but it should be remembered that the HI group did display a developmental trend in speaking skills.…”
Section: Listener Skillsmentioning
confidence: 99%
“…It therefore appears that a failure to take the listener's need into account is a problem that is experienced by some HI children, and may be more likely to occur as level of hearing loss increases (Elfenbein et al, 1994). The ability to take a listener's needs into account develops throughout the school years (Jeanes et al, 2000). Whether some HI children's inability to take the listener's needs into account is due to a developmental lag in referential communication skills or some other explanation cannot be determined from these results, but it should be remembered that the HI group did display a developmental trend in speaking skills.…”
Section: Listener Skillsmentioning
confidence: 99%
“…Owens (1996) showed that hearing children acquire these skills within the first 8 years of life through conversational interactions. However, for profoundly deaf children, learning the rules of social communication is more challenging (Crocker & Edwards, 2004) and many have difficulties in acquiring pragmatic skills necessary for communicating with hearing people, particularly when using the spoken modality (Bench, 1992;Jeanes, Nienhuys & Rickards, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced quality and quantity of interactions means fewer opportunities for these behaviours to be modelled and fewer opportunities for the deaf child to apply the behaviours in natural settings (Brackett, 1983;Carney & Moeller, 1998;Jeanes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jeanes et al (2000) investigated the ability of two groups of profoundly deaf students born to hearing parents, one group using oral and the other using signed communication, to employ a series of pragmatic skills required for effective face-to-face interaction; for example, the ability of listeners to request clarification, the ability of speakers to respond to requests, and the strategies speakers use at times of communication breakdown. They found that profoundly deaf students had difficulty consistently using appropriate, productive pragmatic behaviors in their face-to-face dyadic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Second, some studies evaluate deaf children's pragmatic abilities from the point of view of individuals who speak a verbal language. In particular, such studies focus on the quantity of specific and non-specific requests for clarifications made by hearing and deaf children (see Jeanes et al, 2000). They do not analyze the appropriateness of the responses in terms of their effectiveness.…”
Section: Introductionmentioning
confidence: 99%